Medical education quality assessment. Perspectives in University Policlinic context. - Maricel Castellanos González; Jorge Cañellas Granda; Iraldo Mir Ocampo; Miguel Aguila Toledo (Medisur)
Quality has currently a central role within our National Health System, particularly in the formative process of human resources where we need professionals more prepared every day and ready to face complex tasks. We make a bibliographic review related to quality assessment of educational process in health system to analyze the perspectives of the new model of University Policlinic, formative context of Medical Sciences students.